UPAYA MENINGKATKAN KETERAMPIAN CHEST PASS BOLA BASKET MELALUI STRATEGI VARIASI MENGAJAR SISWAKELAS X IPA 7 SMAN 1 PANGKALAN KERINCI KABUPATEN PELALAWAN - Mohd Agung Pratama; Oki Candra (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2019)
The purpose of this study was to find out whether through teaching variation strategies can improve chest pass learning in basketball games. With research subjects 36 students. This research is a CAR research. Samples from this study were 36 students 18 male students and 18 female students. Based on data processing that researchers have done in class X Science 7 of SMAN 1 Pangkalan Kerinci, from a total sample of 36 students, it was concluded that in this study a complete 33 students with a percentage of 91.7% and an incomplete number of 3 people with a percentage of 8.3%. Based on the results of the research data analysis that has been done, it can be concluded that the application of variations in teaching in the learning process can improve the skills of basketball pass chest pass in class X Science 7 students at SMAN 1 Pangkalan Kerinci.